2011
DOI: 10.1103/physrevb.83.193302
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emergence of a persistent spin helix from homogeneous spin polarization

Abstract: We demonstrate that a homogeneous spin polarization in one-dimensional structures of finite length in the presence of Bychkov-Rashba spin-orbit coupling decays spontaneously toward a persistent spin helix. The analysis of formation of spin helical state is presented within a novel approach based on a mapping of spin drift-diffusion equations into a heat equation for a complex field. Such a strikingly different and simple method allows generating robust spin structures whose properties can be tuned by the stren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
5
19
0
Order By: Relevance
“…We see that the "Doppler shifts" are different for the two helical components. Recall that the helical mode S − describes the "persistent spin helix" in the balanced case, 33,[75][76][77][78][79][80] when the wave vector q of the grating matches the SOC wave vector q 1 . In recent experiments by Yang et al 32,44 the time evolution of the spatial phase has been measured by Doppler velocimetry.…”
Section: B Spin Grating With Q E: Helical Doppler Effectmentioning
confidence: 99%
“…We see that the "Doppler shifts" are different for the two helical components. Recall that the helical mode S − describes the "persistent spin helix" in the balanced case, 33,[75][76][77][78][79][80] when the wave vector q of the grating matches the SOC wave vector q 1 . In recent experiments by Yang et al 32,44 the time evolution of the spatial phase has been measured by Doppler velocimetry.…”
Section: B Spin Grating With Q E: Helical Doppler Effectmentioning
confidence: 99%
“…where κ n = 1/(4τ 2 ) − π 2 n 2 v 2 /L 2 . Previously, we investigated the spin relaxation in finite length wires in the diffusive regime and found that an initially homogeneous spin polarization in z direction transforms into a persistent spin helix at long times 28 . The same qualitative result follows from Eq.…”
Section: Relaxation Of Homogeneous Polarization In Finite Length Wmentioning
confidence: 99%
“…These examples include investigations of spin relaxation in 2D channels, [17][18][19][20][21][22] 2D half-space, 23 2D systems with antidots, 24 large quantum dots, 25,26 and one-dimensional (1D) finite-length wires. 27 Both available experimental and theoretical results indicate that, typically in the diffusive spin transport regime, the electron spin life time is longer in systems with boundaries.…”
Section: Introductionmentioning
confidence: 99%